Increase of lipid peroxidation in rat liver microsomes by dehydroepiandrosterone feeding - Świerczyński, Julian; Bannasch, Peter; Mayer, Doris (Biochimica et biophysica acta, 1996)
Oral administration of the adrenal steroid dehydroepiandrosterone (DHEA), a peroxisome proliferator and hepatocarcinogen in the rat, caused an increase in NADPH-dependent lipid peroxidation in microsomes isolated from rat liver and kidney cortex, but not from brain. The increase of liver microsomal lipid peroxidation was greater in male than in female rats. The effect of DHEA on lipid peroxidation became discernible after feeding steroid-containing diet (0.6%) to male and female rats for 2 and 3 days and reached maximal levels at 1 and 2 weeks, respectively. The increase of microsomal lipid peroxidation reached a plateau stimulation at 0.05% in the diet. The addition of DHEA in the concentration range 0.1-100 μM to microsomes isolated from control rats had no effect on lipid peroxidation. Furthermore, a significant increase of the endogenous concentration of thiobarbituric acid reactive substances was found in microsomes after DHEA-administration at 0.05% in the diet. These results provide in vivo evidence that DHEA can cause lipid peroxidation in rat liver. Administration of DHEA at 0.6% in the diet for 7 consecutive days also significantly enhanced NADH- and ascorbate-dependent lipid peroxidation in liver microsomes. The DHEA-stimulated rat liver microsomal lipid peroxidation was completely inhibited by EDTA but not by superoxide dismutase, catalase or mannitol applied as OH-radical scavenger. The findings indicate that membrane lipid peroxidation is an early effect of DHEA, and that this process may be involved in the steroid-induced carcinogenesis in rats.